Assessment of nuclear radiation pollution in uranium mining-impacted soil - Hussein Houmady, Raad Obid (Iraqi Journal of Physics, 2019)
Activities associated with mining of uranium have generated significant quantities of waste materials containing uranium and other toxic metals. A qualitative and quantitative study was performed to assess the situation of nuclear pollution resulting from waste of drilling and exploration left on the surface layer of soil surrounding the abandoned uranium mine hole located in the southern of Najaf province in Iraq state. To measure the specific activity, twenty five surface soil samples were collected, prepared and analyzed by using gamma- ray spectrometer based on high counting efficiency NaI(Tl) scintillation detector. The results showed that the specific activities in Bq/kg are 37.31 to 1112.47 with mean of 268.16, 0.28 to 18.57 with mean of 6.68 and 132.25 to 678.33 with mean of 277.49 for 238U, 232Th and 40K respectively. Based on these values, radium equivalent activity in Bq/kg and absorbed dose rate one meter above the ground surface nGy/h were calculated and found to be vary 52.72 to 1189.84 and from 25.02 to 553.01. The indoor and outdoor annual effective dose rate in mSv/y ranged from 0.12 to 2.71 and from 0.03 to 0.67 respectively. To evaluate the dangerous of the study area, the external (Hex) and internal (Hin) hazard indexes are calculated and found to be ranged 0.14 to 3.21 and from 0.24 to 6.22. For the purpose of assessing the seriousness of the study area, results were compared with the world wide average. This comparison indicated that the study area is not safe from the radiological protection point view.